Nursing students’ lived experiences of multicultural nursing education: A phenomenological study - Edison Kabak (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Cultural diversity in healthcare necessitates that nursing students possess the ability to comprehend the diverse values, beliefs, and practices of patients. Understanding how nursing students experience multicultural education is important for developing cultural competence, effective communication, and culturally sensitive professional attitudes. Purpose: To explore nursing students’ lived experiences and their interpretation of multicultural nursing education. Method: A qualitative approach with a phenomenological design. A total of 12 diploma nursing students were selected by purposive sampling as participants. Data were collected through semi-structured in-depth interviews and analyzed phenomenologically through the process of meaning identification, thematic grouping, and experiential interpretation. Results: The results of the study produced five main themes, namely cultural awareness as the basis for learning, experience of adaptation to cultural differences, the role of lecturers in learning, communication challenges in clinical practice, and the formation of professional attitudes based on cultural sensitivity. The findings suggest that the meaning of multicultural nursing education is formed through classroom learning experiences and clinical practice. Conclusion: Multicultural nursing education plays an important role in shaping students' cultural competencies, including awareness, adaptability, communication, and professional attitudes. The integration of multicultural learning in the curriculum is necessary to prepare students to deal effectively with the diversity of patients.